2020
DOI: 10.4062/biomolther.2019.047
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Probenecid on Osteoclast Formation via JNK, ROS and COX-2

Abstract: Probenecid is a representative drug used in the treatment of gout. A recent study showed that probenecid effectively inhibits oxidative stress in neural cells. In the present study, we investigated whether probenecid can affect osteoclast formation through the inhibition of reactive oxygen species (ROS) formation in RAW264.7 cells. Lipopolysaccharide (LPS)-induced ROS levels were dose-dependently reduced by probenecid. Fluorescence microscopy analysis clearly showed that probenecid inhibits the generation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…ROS are critical intracellular signaling mediators that connect OC essential genes function, as well as the key regulator of cellular redox state that determines the post-translational modification of protein kinases and phosphatases in OC [ 46 , 47 ]. In the current study, the level of ROS in BMMs boosted obviously due to LPS stimulation, which is similar to other reports [ 48 ]. As the defense system, antioxidant enzymes, could balance the ROS formation, resulting in redox homeostasis within the cell [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…ROS are critical intracellular signaling mediators that connect OC essential genes function, as well as the key regulator of cellular redox state that determines the post-translational modification of protein kinases and phosphatases in OC [ 46 , 47 ]. In the current study, the level of ROS in BMMs boosted obviously due to LPS stimulation, which is similar to other reports [ 48 ]. As the defense system, antioxidant enzymes, could balance the ROS formation, resulting in redox homeostasis within the cell [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…[56] Furthermore, it has been experimentally used for protection against nephrotoxicity. [35] Several explanations have been suggested through the inhibition of either the ROS/JNK pathway [34] or multidrug-resistance-associated protein 4 (MRP4). [57] Cheng and Kim reported that Prob inhibits COX-2 expression and uric acid concentration in metabolic bone disorders (i.e., osteoarthritis, osteoporosis, and rheumatic arthritis).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Prob can inhibit COX-2 expression and uric acid concentration in metabolic bone disorders. [34] To this end, the current study evaluated the use of Prob in BPH as a COX-2 inhibitor.…”
mentioning
confidence: 99%
“…Probenecid is a compound with a molecular weight of 285.36 Da, and its molecular formula is C 13 H 19 NO 4 S, which has been used for the treatment of gout clinically ( Cheng and Kim, 2020 ). Probenecid has been found to inhibit oxidative stress in neuronal cells ( Cheng and Kim, 2020 ) and also acts as a pannexin-1 channel inhibitor, which may inhibit the activation of inflammasomes ( Silverman et al, 2009 ), as well as being protective in a rat model of cognitive impairment ( Cheng and Kim, 2020 ). These reports suggest that probenecid is therapeutic for CNS injury.…”
Section: Discussionmentioning
confidence: 99%
“…Probenecid, a sulfonamide derivative approved for use in 1951, has been used to treat gout and its adverse effects, and pharmacokinetics have been intensively studied ( Baranova et al, 2004 ; Papadopoulos and Verkman, 2008 ). One study found that oxidative stress in nerve cells can be effectively inhibited by probenecid ( Cheng and Kim, 2020 ). Another study showed that probenecid also acts as a pannexin-1 channel inhibitor and may inhibit the activation of inflammasomes ( Silverman et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%